2012
DOI: 10.1115/1.4006951
|View full text |Cite
|
Sign up to set email alerts
|

Finite Displacement Screw Operators With Embedded Chasles’ Motion

Abstract: Rigid body displacement can be presented with Chasles’ motion by rotating about an axis and translating along the axis. This motion can be implemented by a finite displacement screw operator in the form of either a 3 × 3 dual-number matrix or a 6 × 6 matrix that is executed with rotation and translation as an adjoint action of the Lie group. This paper investigates characteristics of this finite displacement screw matrix and decomposes the secondary part that is the off diagonal part of the matrix into the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…It actually took some time until their relation was fully understood since Ball [8][9][10] introduced the concept of screws. An excellent review on this topic can be found in [47,48]. With a chosen reference frame, a general screw is represented by a screw coordinate vector X = (ξ , η), as in (5), where ξ ∈ R 3 is the angular and η ∈ R 3 is the translational component.…”
Section: Instantaneous Screws and Canonical Coordinatesmentioning
confidence: 99%
“…It actually took some time until their relation was fully understood since Ball [8][9][10] introduced the concept of screws. An excellent review on this topic can be found in [47,48]. With a chosen reference frame, a general screw is represented by a screw coordinate vector X = (ξ , η), as in (5), where ξ ∈ R 3 is the angular and η ∈ R 3 is the translational component.…”
Section: Instantaneous Screws and Canonical Coordinatesmentioning
confidence: 99%
“…For example, the finite screw of RRPRR dose not equal to Eq. (22) In this way, five 5-DOF TPM limb structures can be generated and denoted by PRRRR, RPRRR, RRPRR (Eq. (21), RRRPR and RRRRP, respectively.…”
Section: -Dof Tpm Limb Structures Without Inactive R Jointmentioning
confidence: 99%
“…Fig. 1, general finite motion of a rigid body moving from pose 1 to pose 2 can be represented by a finite screw f S in terms of a rotation about an axis followed by a translation along the same axis [18,22,25]. The axis is referred to as the Chasles' axis or the finite screw axis [21,[24][25][26][27], and hereafter we refer the axis as screw axis for simplicity.…”
Section: Parametric Representation Of Finite Motions Of a Tpmmentioning
confidence: 99%
See 2 more Smart Citations